Bird-women on the Harpy Monument from Xanthos, Lycia: sirens or harpies - Draycott, C (Archaeopress, 2008)
The initial identification of the bird-women on the Harpy Monument as the eponymous 'harpies' has long been superseded by the identification of the creatures as sirens. The small figures they are shown carrying have often been seen as eidola or souls of the deceased. This in turn has led to the idea that one of the functions of sirens was to transport the souls of the deceased to the afterlife. However, there is every reason to believe that the images show an abduction image, related to contemporary images of sphinxes carrying off young males. It is unusual in that the figures they abduct are female, and in this the images actually do recall the legend of the harpies abducting the daughters of Pandareos, which led to the initial naming of the tomb. Although they may not be adequately labelled as 'harpies' or 'sirens', their role as shown here is closer to the former than the latter.